URGENSI HOSPITALITAS KRISTIANI DALAM MEWUJUDKAN MODERASI BERAGAMA DITENGAH MASYARAKAT MULTIKULTURAL - Tembang, Setblon (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: This research is motivated by the rise of extreme religious attitudes and practices, which have an impact on the many conflicts between religious believers in multicultural societies. In response to this, efforts are needed to prevent conflict between religious communities by living a moderate lifestyle. Religious moderation is a balanced perspective, attitude, and religious practice. This research was conducted using a literature-based descriptive method. This research aims to offer efforts to realize religious moderation in a multicultural society based on Christian hospitality in John 4:1-30. The results of this research show that Jesus showed an example of practicing hospitality in realizing a moderate attitude in religion amidst the socio-religious disruption of Jews and Samaritans through dialogue. Jesus attempted reconciliation in the midst of the tense conflict between the Jews and Samaritans. This is a form of hospitality that reflects a moderate attitude in religion: enemies who become friends. Christian hospitality within the framework of religious moderation seeks to deny excessive fanaticism that leads to fundamentalism and radicalism but embraces differences and builds friendship. This is an important pillar in building unity and integrity in a multicultural society. Abstrak: Penelitian ini dilatarbelakangi oleh maraknya sikap dan praktek beragama yang ekstrim yang berdampak pada banyaknya konflik antar pemeluk agama dalam masyarakat multikultural. Merespon hal itu, dibutuhkan upaya untuk mencegah konflik antar umat beragama dengan cara hidup moderat. Moderasi beragama merupakan cara pandang, sikap dan praktek beragama yang seimbang. Penelitian ini dilakukan dengan menggunakan metode deskriptif berbasis literatur. Penelitian ini bertujuan untuk menawarkan upaya mewujudkan moderasi beragama di tengah masyarakat multikultural berdasarkan hospitalitas Kristiani dalam Yohanes 4:1-30. Adapun hasil penelitian ini yaitu Yesus menunjukkan keteladanan dalam mempraktekkan hospitalitas dalam mewujudkan sikap moderat dalam beragama di tengah disrupsi sosial-religi orang Yahudi dan Samaria melalui dialog. Yesus berupaya melakukan sebuah rekonsiliasi di tengah ketegangan konflik antara orang Yahudi-Samaria. Inilah bentuk hospitalitas yang merefleksikan sikap moderat dalam beragama, musuh yang menjadi sahabat. Hospitalitas Kristiani dalam bingkai moderasi beragama berupaya menafikkan fanatisme berlebih yang mengarah pada fundamentalisme dan radikalisme, tetapi merangkul perbedaan dan membangun persahabatan. Hal inilah yang menjadi pilar penting dalam membangun persatuan dan kesatuan di tengah masyarakat multikultural.